Non-thyroid Neoplastic Neck Swelling Clinical and Histopathological Evaluation (TAJ: Journal of Teachers Association, 2009)
With a view to cast a glance on pattern of non-thyroid neoplastic neck swelling a descriptive study was conducted among 54 cases irrespective of age and sex. It was observed that 85.2% non-thyroid neoplastic masses were malignant and of which 78.3% metastatic, and among them 80.6% were supraclavicular in origin. Among primary malignancy 90% were lymphomas and 37.5% of benign neoplasm were pleomorphic adenoma. Histopathologically 72.2% secondary tumours were squamous cell carcinoma. doi: 10.3329/taj.v21i2.3796 TAJ 2008; 21(2): 152-154